The Descriptive Analysis of Perceptions of ITTP Data Science Students regarding Face-to-Face Learning Plans - Wahyu Nouval Aghniya; Lutfhi Rakan Nabila; Rizky Ananda Putra (Research Group of Data Engineering, Faculty of Informatics, 2023)
The case of Covid-19 which has been going up and down has forced educational units to think about what learning methods will be applied in the future and also have to pay attention to the responses that students will say. Remember, some students have various arguments, including students who can think maturely in assessing something related to their future interests. This research was conducted with the aim of knowing student perceptions regarding face-to-face learning plans during the pandemic at IT Telkom Purwokerto. In knowing each student's perception, there are several variables that can influence the results of their perception. For the population in this study, all undergraduate students of the IT Telkom Purwokerto Faculty of Informatics in 2021 with judgment/expert sampling as the sampling technique. The instrument used is a questionnaire or questionnaire. The data analysis method used in this research is descriptive quantitative analysis method. Based on the research that has been done, the results show that there were 37 answers (56.1%) who strongly agreed with the question regarding facilities & infrastructure, for Regarding service quality, there were 45 answers (68.2%) who strongly agreed, then for questions regarding student perceptions, there were 17 answers (25.8%) who felt strongly agreed. And obtained results of less than 15% and even up to 0% in each variable for answers that do not agree. So, most students agree with face-to-face learning and attending lectures. Likewise with the parents of each student who agreed to the plan.